Trends in Invasive Melanoma Thickness in Norway, 1983-2019 - Raju Rimal; Trude E. Robsahm; Adele C. Green; Reza Ghiasvand; Corina S. Rueegg; Assia Bassarova; Petter Gjersvik; Elisabete Weiderpass; Odd O. Aalen; Bjørn Møller; Flavie Perrier; Marit B. Veierød (Medical Journals Sweden, 2024)
Monitoring melanoma incidence time trends by tumour thickness is essential to understanding the evolution of melanoma occurrence and guiding prevention strategies. To assess long-term incidence trends, tumour thickness was extracted from pathology reports in the Cancer Registry of Norway (1983-2007) and the Norwegian Melanoma Registry (2008-2019), n = 45,635 patients. Across all anatomic sites, T1 (≤ 1 mm) incidence increased most (men annual percentage change [AAPC] = 4.6, 95% confidence interval [95% CI] 4.2-5.0; women AAPC = 3.2, 95% CI 2.8-3.6); the increase was steep until 1989/90, followed by a plateau, and a further steep increase from 2004/05. Increased incidence was also observed for T2 (>1.0-2.0) melanoma (men AAPC = 2.8, 95% CI 2.4-3.2; women AAPC = 1.5, 95% CI 1.1-1.9), and T3 (>2.0-4.0) in men (AAPC = 1.4, 95% CI 0.9-1.9). T4 (>4.0) melanoma followed a similar overall pattern (men AAPC = 1.3, 95% CI 0.9-1.7, head/neck, upper limbs, and trunk; women AAPC = 0.9, 95% CI 0.4-1.4, upper limbs and trunk). Men had the highest T3 and T4 incidence and the sex difference increased with age. Regarding birth cohorts, age-specific incidence increased in all T categories in the oldest age groups, while stabilizing in younger patients born after 1950. Overall, the steep increase in T1 melanoma was not accompanied by a decrease in thick melanoma.